Kepuasan Kerja Tenaga Pendidik di Lembaga Pendidikan Islam - Noviyanti, Shobihatul Fitroh; Ulfiandi, Ihsan Zikri; Wahananto, Juri; Amrullah, Addul Malik Karim (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2023)
This article discusses the job satisfaction of teaching staff at Islamic Education Institutions, what things need to be considered in triggering job satisfaction. Different categories of job satisfaction include satisfaction with salary, promotions, supervision satisfaction, co-worker satisfaction, satisfaction with the job itself. , altruism, status, and environment. The research method used in this article is a qualitative research method with a library research approach. The library research approach itself is an approach to qualitative research methods that takes data from reading media. The results of this research are factors that can influence teacher job satisfaction, starting from psychological factors, social factors, and financial factors.